Sembène Ousmane's Xala: The Use of Film and Novel as Revolutionary Weapon - Kenneth Harrow (Studies in 20th & 21st Century Literature, 1980)
Sembène Ousmane's Xala was written as a novel and made into a film in 1974. It is a biting attack upon the newly risen bourgeois class that has ascended to power and wealth in Senegal since independence. The ideological framework of Xala rests upon Marxist assumptions adapted to and modified by the circumstances in Africa. The distinctively Senegalese features which mark Sembène's portrayal include Muslim and traditional religious beliefs which form the basis of the class oppression and the sexism depicted in Xala. They also supply the title to the work since xala means impotency in Wolof, and it is described with great humor by Sembène, as the result of a marabout's curse. Sembène's treatment of the theme of class oppression focuses upon the great disparities that exist between the wealthy, elite classes and the impoverished masses, especially the beggars and cripples who live on the streets of Dakar. By focusing upon the issue of acculturation in the film, and by emphasizing the importance of imagery related to sight and the act of seeing, Sembène effectively overcomes the deficiencies of the novel in creating the film version of Xala.
Keywords: Sembène Ousmane; Xala; film; novel; bourgeois; Marxism; sexism; oppression; classes; impoverishment; imagery; sight; act of seeing